Análise dos conflitos ambientais no campo do abastecimento de água : um estudo de caso em São Tomé das Letras - Minas Gerais - Bárbara Furtado Barra (2023)
This work aims to analyze the environmental conflict in the field of water supply. For this purpose, a qualitative and empirical study was defined, using the case study as the method of investigation. The chosen case study was the rural community of Cantagalo in São Tomé das Letras, Minas Gerais. This case study was based on observing water scarcity and disputes over water during dry periods among residents with individual water supply solutions. In the same watershed, there is water extraction by the Minas Gerais Sanitation Company (Copasa), which only serves the urban population of the municipal headquarters. The water conflict involves the population's and some councilors' demand for the protection and multiple uses of the Cantagalo stream, located in the rural area of the municipality. This work seeks to engage with scholars of environmental conflicts using Bourdieu's critical sociology and political ecology. The objective is to evaluate the environmental conflicts associated with water supply, intensified by economic activities and multiple water uses. Semi-structured interviews, participant observation, and documentary analysis were used for data collection, Through the strategies of the actors involved in the conflict, it was observed that there is a claim for conflict categorization, which was denied by technical rationality, as the subjects do not fit the category proposed in the legal and technical instrument due to the limitations of the instrument regulating water resource use and the declaration of conflict areas by the responsible environmental agency. Additionally, they undergo a process of obliteration and delegitimization through institutional discourses. Furthermore, by using the theoretical lens of the human right to water, from the perspective of water as a collective good, disparities in water access between urban and rural populations were identified, along with violations of the human right to water. In São Tomé das Letras, the water conflict is analysed through geographical conditions from a managerial and technical perspective, resulting in inequalities. Technical arguments are maintained without delving into the various dimensions within the established local reality. Political-legal arrangements and water inequalities must be increasingly understood as the outcome of mutually constituted interactions among various social, economic, political, and physical factors.